PEMANFAATAN DAUN NANAS (ANANAS COMOSUS) SEBAGAI ADSORBEN LOGAM Ag DAN Cu PADA LIMBAH INDUSTRI PERAK DI KOTAGEDE YOGYAKARTA - Ardi Yuli Wardani (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
This research aims to determine the characteristics, the adsorption and the influence ofthe adsorbent from the leaves of pineapple (Ananas comosus) on the adsorption of metal Agand Cu.The study is a basic experimental research. The subject the research is carbon from thepineapple leaves activated by the HCl 15% with a 24 hour immersion time. This researchinvolved three steps. They are making carbon activated from pineapple leaves, characterizingthe activated carbon and determine the adsorption towards Ag and Cu metal in the wastewater of silver electroplating industry in Kotagede. The object of the research is the ability ofthe adsorbent from the pineapple (Ananas comosus) leaves for Cu and Ag adsorbs metalsfrom the waste water of the silver industries in the town. The independent variable used isthe amount of activated carbon, namely 0.5, 1.0, 1.5, 2.0 and 2.5 grams per 100 mL of liquidwaste. Time and pH on the adsorption were carried out under optimum conditions, the contacttime of 24 hours and at pH 2. The characterization of the activated carbon used the parametersof the water content, ash and absorption of I2. The adsorption was determined by comparingthe concentrations of Cu and Ag before and after the adsorption .The research findings showed that the activated carbon from the pineapple (Ananascomosus) leaves consisted of 0.6% of moisture content, 3.2% of ash content and theabsorption of I2 73.67%. For Cu the optimum adsorption was obtained in the adsorbentmass of 2 gram/100 mL with the adsorption power of 69.07% and for Ag the optimumadsorption was obtained in the adsorbent mass of 1.5/100 mL with the adsorption power of74.56%. The increase in mass of adsorbent increased the adsorption power.Key words: adsorbents, pineapple leaf, liquid waste